2019
DOI: 10.11591/ijece.v9i6.pp5865-5175
|View full text |Cite
|
Sign up to set email alerts
|

Insight on face liveness detection: A systematic literature review

Abstract: <p>To review researcher’s attempts in response to the problem of spoofing and liveness detection, mapping the research overview from the literature survey into a suitable taxonomy, exploring the basic properties of the field, motivation of using liveness detection methods in face recognition, and Problems that may restrain the advantages. We presented a subjected search on face recognition with liveness detection and its synonyms in four main databases: Web of science, Science Direct, Scopus and IEEE Xpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The accuracy of that system was 96.2%. Raheem et al [12] proposed many stages that used several methods such as agglomerative hierarchical clustering and LBP. In an image that contained multiple faces, they used content based image retrieval (CBIR), which is characterized by the same image property.…”
Section: Review Of Existing Methodsmentioning
confidence: 99%
“…The accuracy of that system was 96.2%. Raheem et al [12] proposed many stages that used several methods such as agglomerative hierarchical clustering and LBP. In an image that contained multiple faces, they used content based image retrieval (CBIR), which is characterized by the same image property.…”
Section: Review Of Existing Methodsmentioning
confidence: 99%
“…The third step is the eligibility process. In this study, all of the articles that were found were checked manually to make sure that after the screening process, all of the remaining articles met the criteria [41]. The procedure was completed by reading the titles and abstracts of the selected papers.…”
Section: Eligibilitymentioning
confidence: 99%
“…"There are very scarce systematic literature reviews (SLR)" obtainable in the ILD research area to the best of our knowledge. The study [17] is one of the current and important SLR providing a good outline of liveness detection techniques to face antispoofing. Furthermore, the study enhances value to the literature by contributing valued perceptions into various liveness detection techniques and face anti-spoofing techniques.…”
Section: Prior Researchmentioning
confidence: 99%